2020
DOI: 10.1088/1742-6596/1660/1/012037
|View full text |Cite
|
Sign up to set email alerts
|

A novel spectral method indirectly to estimate the lead in Cu-Zn-Pb bronze alloy

Abstract: Lead is used in many industrial products, including alloys, because of its importance in improving physical and chemical properties. In this study, a sensitive, simple, economical, fast and accurate, an indirect spectral analytical method was developed using Eriochrome Black T as chelating agent without use of separation and isolation to estimate the amount of lead in the Cu-Zn-Pb bronze alloy by using UV-Visible spectrophotometer instrument. The accuracy of the method was 99.97 ± 0.35 and the limits of detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…1and fig.2 in this study. And the wavelengths of greatest absorption of complexes Al(III) ethanolamine and Zn(II) cyanide are 412 and 300 nm respectively (Serih, 2020).…”
Section: Compoundmentioning
confidence: 99%
See 1 more Smart Citation
“…1and fig.2 in this study. And the wavelengths of greatest absorption of complexes Al(III) ethanolamine and Zn(II) cyanide are 412 and 300 nm respectively (Serih, 2020).…”
Section: Compoundmentioning
confidence: 99%
“…Quantitative analysis of lead in leaded aluminum alloy is performed by measuring the decrease in the absorbance of the EBT by the new developed method based on the calculation of the difference between the absorbance of EBT at its initial concentration (A Lₒ ) and its absorbance at residual concentration (A Lr ) as a result of its reaction with lead ions in the sample solution by using standard addition method and application of the following equation: Studies indicated that (Wang et al, 2018;Serih, 2020) the molar ratio of Pb(II):EBT is 1:1. They contributed to the development of our new method for determining lead in the leaded aluminum alloy as shown in table 2 and figure 4 In general (Serih, 2020)…”
Section: Quantitative Studymentioning
confidence: 99%